The Effectiveness of Psychodynamic Psychotherapy With Schizophrenic Psychoses: A Modified Systematic Literature Review - Josias, Moira (Auckland University of Technology, 2009)
This dissertation seeks to determine whether psychodynamic psychotherapy is an effective treatment for schizophrenic psychoses. This study begins by exploring the historical construction of the term ‘schizophrenia’ and historical treatment approaches to schizophrenic psychoses. The research uses a modified literature review and although it does not contain case material, it does at times refer to the author’s general experience within the area of mental health. The advantages and disadvantages of biological and psychosocial treatments both past and present, for schizophrenic psychoses are discussed. The possible causation of schizophrenia is also investigated and recent research regarding this considered. Little research has been done in the areas of the effectiveness of psychodynamic psychotherapy with schizophrenia and psychosis, and all studies concerning this are controversial. However, a significant body of clinical literature has accrued from psychotherapists who have achieved success in working with clients diagnosed with schizophrenia/psychosis. Although the results and findings regarding the effectiveness of psychodynamic psychotherapy have often been inconsistent and inconclusive, some recent literature, anecdotal reports from psychotherapists and my own personal experience as a therapist all suggest that psychodynamic psychotherapy can play an effective part in working with psychosis, as a component of treatment with additional psychosocial and biological interventions, or as the sole mode of treatment, or as an adjunct to treatment with medication. In researching this dissertation topic, a key theme that emerged is the importance of multiple disciplines working together for the good of the client rather than believing there is only one way of treating this particular client group.
Keywords: Schizophrenia; Psychosis; Schizophrenic; Psychotherapy; Psychoses; Psychodynamic